THE INFLUENCE OF GREEN ACCOUNTING, CARBON EMISSION DISCLOSURE, AND PROFITABILITY ON COMPANY VALUE - Ridwan; Eddi Dj Wibowo; Abdullah Ramdhani; Jusni Samsulma'arif; Ai Rini Rianti (ZILLZELL MEDIA PRIMA, 2026)
A company's value reflects how the market assesses a company's performance and prospects. In the mining sector, environmental issues increase the relevance of green accounting and carbon emission disclosure, but the extent to which investors respond to this information is still inconsistent. This study aims to analyze the influence of green accounting, carbon emission disclosure, and profitability on the value of companies in mining companies listed on the Indonesia Stock Exchange for the 2021–2023 period. The study used a causal associative quantitative approach with purposive sampling techniques and produced 84 firm-year observations. Data analysis was carried out through descriptive statistics, classical assumption tests, and multiple linear regression. The results of the study show that green accounting and carbon emission disclosure do not have a significant effect on the company's value, while profitability has a positive and significant effect. These findings indicate that the market still places more emphasis on financial performance than environmental disclosure in assessing mining companies. The implications of the study show that environmental initiatives will contribute more to the company's value if successfully converted into operational efficiency, risk reduction, and strengthening profitability.